Efektivitas Ekstrak Daun Pacar Air (Impatiens balsamina L.) Untuk Meningkatkan Respon Imun Non Spesifik Ikan Nila (Oreochromis niloticus) - Pasaribu, Wesly; Longdong, Sammy N.J (e-Journal BUDIDAYA PERAIRAN, 2015)
The objective of this research was  to determine the most effective dose and the best induction time of  Impatiens balsamina extract in enhancing nonspesific immune response of nile tilapia (Oreochromis niloticus).  The tested fish were nile tilapia, 14-16 cm in length, and  39-42 g in weight, obtained from Balai Pengembangan dan Pembinaan Pembudidayaan Ikan (BP3I) Tateli. The  research was designed in 2x4 factorial in completely randomized design.  There were  two factors   tested  in this research, the dose  and  time.  There were four levels of dose,  A1 = 0 mg/mL extract, A2= 30 mg/mL extract, A3= 50 mg/mL extract, A4= 70 mg/mL extract; and there were  two levels of time,  B1= 7 days after injection and B2=14 days after injection.   The extract was injected intramuscularly  with a dose of  0.2 mL per fish.   Data collected in this research was the immune parameters (total leucocyte count and phagocytosis activity). The results showed that the most effective dose in enhancing nonspesific immune response was   A1=50 mg/mL extract and the best induction time was  B1= 7 day after injection.   The results also indicated  that there was significant  interaction between  dose and time in influencing  the total amount of leucocyte, but there was not  interaction in influencing the phagocytic activities. Keywords : Impatiens balsamina, immune Response, total leucocyte count, phagocytosis activity.